Demography and findings of reported rape cases - Quader, MM; Rahman, MH; Kamal, M; Ahmed, AU; Saha, SK (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Jan;19(1):32-36. The abstract of this article is available on the PubMed website